Data Management Plan in university Data Repositories - Souza de Aguiar Monteiro, Elizabete Cristina de [UNESP]; Goncalves Sant'ana, Ricardo Cesar [UNESP] (Univ Federal Santa Catarina, 2018)
Data Management Plan is the formal document that describes the data management processes integrating their life cycle. The elaboration of the Data Management Plan assists the researchers and professionals working in the repositories. The objective of this study was to investigate how many and which data repositories of the world's 100 best universities provide Data Management Plans and identify aspects related to possible benefits generated by their use. The methodology was based on documental and exploratory research of a qualitative and quantitative nature. The exploratory methodology was used to survey the universities through the webometrics.info website and its repositories. The results show that only 36 repositories make available Data Management Plans and that their instructions vary depending on the characteristics of the repositories and the data sets deposited in them. It is concluded that its use provides several benefits to all actors involved in data management such as the indication that the data controllers should be mentioned, highlighting the value of the collection work, the maximization of data reuse, the indication of which licenses are assigned to the datasets, which determines how the data is licensed and the forms of data collection, use and guidance on data privacy issues.
Keywords: Data Management Plan; Data management; Search data; Data repository; Data Life Cycle